A teaching proposal on the new water culture for students aged 14–15: design, application and evaluation in a Colombian context - Castro-Velásquez, Freddy Enrique; Ramírez-Segado, Alejandra; Benarroch, Alicia (Frontiers in Education, 2024)
Education is key for teaching citizens to be aware of the value of water and the importance of using it sustainably. This work analyses the effects of a teaching proposal called Únete a la Nueva Cultura del Agua [Join the New Water Culture] for students aged 14-15 in a Colombian context (Temporal link for doubleanonymized peer review https://doi.org/10.6084/m9.figshare.23515887.v2). It was applied in Social and Natural Science classes over 10 two-hour sessions. It was evaluated through: (a) Pretest-postest questionnaire;(b) follow-up questionnaires on the proposal that included self-evaluation, co-evaluation and hetero-evaluation on the part of students; and (c) student workbooks. The results showed the strengths and weaknesses of the proposal. It is concluded that there is a good correspondence between the strong and weak points of the proposal and the contents of the tasks that received the highest and lowest scores, respectively, revealing the associations between knowledge and perceptions. These associations are corroborated with the entries in the student workbooks following the end of the teaching proposal. Field Code Changed Field Code Changed Formatted: English (US) Formatted: English (US) Field Code Changed